2022
DOI: 10.2478/enr-2022-0021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on adiponectin levels potentially mediated by vitamin D in type 2 diabetic patients

Abstract: Objective. The positive effects of exercise on adiponectin and vitamin D have independently been reported. Recent studies have suggested that vitamin D increases adiponectin synthesis through inhibition of the rennin-angiotensin system in adipose tissue. However, studies evaluating the effects of an aerobic exercise on adiponectin and vitamin D simultaneously investigating the potential mechanism of vitamin D-dependent adiponectin pathways in patients with type 2 diabetes mellitus (T2DM) are still limited. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We identified 946 articles through our database searches and three additional articles were identified through reference list searches. After removing duplicates, the titles and abstracts of 667 articles were screened; 123 full-text articles were assessed for eligibility, 32 were included in the review [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ] and 24 in the meta-analysis [ [22] , [23] , [24] , [25] , [26] , 29 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [40] , [41] , [42] , [43] , [45] , [46] , [47] , [48] , [49] , 51 ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified 946 articles through our database searches and three additional articles were identified through reference list searches. After removing duplicates, the titles and abstracts of 667 articles were screened; 123 full-text articles were assessed for eligibility, 32 were included in the review [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] ] and 24 in the meta-analysis [ [22] , [23] , [24] , [25] , [26] , 29 , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [40] , [41] , [42] , [43] , [45] , [46] , [47] , [48] , [49] , 51 ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In most studies the physical activity interventions were supervised but two home-based physical activity programs were unsupervised [ 26 , 40 ] and two studies had both supervised training sessions and unsupervised home-based sessions [ 39 , 44 ]. Six studies did not clearly state whether the physical activity sessions were supervised or not [ 36 , 38 , [46] , [47] , [48] , 52 ]. The frequency of the physical activity interventions ranged from once a week to once daily, with the length of each session ranging from 30 to 75 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…121 It is also reported that aerobic exercise can help to promote the vitamin D-mediated elevation of adiponectin level in T2DM. 122 Moreover, a single intramuscular injection of vitamin D (300,000 IU) can improve the adiponectin level in gestational diabetes mellitus. 123 Multiple studies have revealed that vitamin D is inversely correlated with the level of proinflammatory cytokines, such as TNFα, interleukin (IL) 1 beta (IL1β), IL6, IL8, IL17A and IL33 (Fig.…”
Section: Role Of Vitamin D In Hepatic Inflammationmentioning
confidence: 99%